2013
DOI: 10.1371/journal.pone.0080746
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Short Isoform Interacts with RRP1B, SIPA1 and Components of the LINC Complex at the Inner Face of the Nuclear Membrane

Abstract: Recent studies suggest that BET inhibitors are effective anti-cancer therapeutics. Here we show that BET inhibitors are effective against murine primary mammary tumors, but not pulmonary metastases. BRD4, a target of BET inhibitors, encodes two isoforms with opposite effects on tumor progression. To gain insights into why BET inhibition was ineffective against metastases the pro-metastatic short isoform of BRD4 was characterized using mass spectrometry and cellular fractionation. Our data show that the pro-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 58 publications
4
58
0
Order By: Relevance
“…Previous studies have suggested that SIPA-1 is involved in certain types of cancer activity, including mutation (23,24), apoptosis (12,25), proliferation (4,15), invasion (15,16) and metastasis (13,26,27). In the present study, it was observed that SIPA-1 additionally regulates bladder cancer cell metastasis and invasion (Figs.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have suggested that SIPA-1 is involved in certain types of cancer activity, including mutation (23,24), apoptosis (12,25), proliferation (4,15), invasion (15,16) and metastasis (13,26,27). In the present study, it was observed that SIPA-1 additionally regulates bladder cancer cell metastasis and invasion (Figs.…”
Section: Discussionsupporting
confidence: 61%
“…For example, BRD4 exists in 2 different isoforms generated by alternative splicing that—in oncology—exert opposite effects. Mass spectrometry revealed that the short isoform is pro-metastatic and also has a broader acetylated histone binding pattern relative to the long isoform 28 . The role of the different isoforms in inflammation has however not yet been explored.…”
Section: Inflammationmentioning
confidence: 99%
“…Accordingly, the level of expression of NET23/STING roughly correlates with the extent of chromatin compaction in the various cell types examined [69]. SUN2 binds the chromatin remodeler BRD4 [70]. LAP2β binds histone deacetylase 3 (HDAC3) [71] and, in co-complex with lamin B1, influences the positioning of several lymphocyte-specific genes [72].…”
Section: The Two Faces Of the Ne — Tissue-specific Impacts On Chromatmentioning
confidence: 99%